1997
DOI: 10.1177/089443939701500206
|View full text |Cite
|
Sign up to set email alerts
|

An Interim Economic Solution to Internet Congestion

Abstract: The current Internet pricing structure and practice of taking traffic on a first-come, first-served basis encourages overuse of the Internet. Users ignore the delay costs they impose on others during periods of congestion, which are increasingly a problem due to the popularity of high-intensity applications such as audio and image. This article describes a system that prioritizes traffic on the Internet and raises revenue for expansion by allowing users to pay to overcome the effects of congestion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…These changes will include the disappearance of flat-rate pricing and the introduction of prices based on the amount of network resources you use, the priority you are willing to pay for, and the time of day you are willing to work. Hazlett (1997) describes these alternatives in detail. Forcing users to make priority and cost decisions will change our use of the Web.…”
Section: Collapse Of the Internet?mentioning
confidence: 97%
“…These changes will include the disappearance of flat-rate pricing and the introduction of prices based on the amount of network resources you use, the priority you are willing to pay for, and the time of day you are willing to work. Hazlett (1997) describes these alternatives in detail. Forcing users to make priority and cost decisions will change our use of the Web.…”
Section: Collapse Of the Internet?mentioning
confidence: 97%
“…The accounting issue is discussed in Hazlett's paper [45]. The dif®culties include the large traf®c volume of the current Internet, the complex routing information, and lack of measurement tools.…”
Section: Wholesale and Retail Pricingmentioning
confidence: 99%
“…Charging the receiver is an interesting and challenging problem [45]. In the current network, data is often sent at the request of the recipient, so it makes sense that the recipient should be charged rather than the sender.…”
Section: Charging the Receivermentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of demanding real-time traffic may seriously threaten the ability of the 'best-effort' service of the Internet to deliver acceptable levels of QoS to many users 2 . To tackle this problem, it has been suggested that traffic produced from different applications can be characterized through an associated payment 2,3,4 . For example, high-volume video may be sent as priority traffic by associating it with a high-priced stream.…”
Section: Introductionmentioning
confidence: 99%